Histories of the Middle East - Yasmin Amin (International Institute of Islamic Thought, 2012)
This collection of papers, presented at a Princeton University conference held in May 2008, opens with an extensive bibliography of Abraham L. Udovitch’s works and a preface detailing his scholarship on the medieval Islamic world’s economic institutions, social structure, legal theory, and practices. The preface also highlights Udovitch’s role and scholarly contributions, prolific publications and international academic collaboration, his respect for interdisciplinary examination and combination of various methods, as well as the diversity of his intellectual pursuits and teachings. The editors praise his visionary approach of focusing on seemingly unconnected texts to uncover the past, such as combining normative legal texts with narratives from diverse sources and genres. His students, as demonstrated in this volume, have adopted these methods. Udovitch’s role in changing the writing of medieval Islamic history is lauded, as is his encouragement to explore new techniques and methodologies as well as his attention to the human experience within history. Mark Cohen, whose introduction examines Udovitch’s many roles (viz., scholar, leading historian, activist, and teacher) provides a biography focused on the professor’s life and projects. The nine essays, loosely grouped into four unmarked categories, discuss the main areas of Udovitch’s interests: (1) “Economic History” highlights the intersections between the legal theory of commerce and the commercial practices of institutions. It includes contributions by Petra Sijpesteijn and Michael Bonner; (2) “Social History” relates economic and social actions, underlines their thematic and methodological commonalities, and comprises essays by Adam Sabra and Jonathan Berkey; (3) “Mediterranean and Indian Ocean” deals with “Middle Eastern History in its Geographic contexts” and coalesces around what has been termed Udovitch’s “Mediterraneanist” concerns, namely, interdenominational relations and negotiations bridging the gap between “rigid principles and supple accommodation.” This includes contributions by Olivia Remie Constable, Yossef Rapaport, and Hassan Khalilieh; and (4) “Urbanism,” the study of cities as sites of economic exchanges and interactions between individuals and groups, combining legal, political, ideological, and intellectual dimensions to form the realities of daily life. This includes two contributions by Boaz Shoshan and Roxani Margariti ...